2021
DOI: 10.9734/jesbs/2021/v34i630338
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Beliefs and Attitudes on Their Children’s Distance Education Performance during the COVID-19 Pandemic in Greek Preschool Settings

Abstract: Background: Current research and the bibliography suggest that both synchronous and asynchronous distance education in the early years of education is a new era to explore the teaching of young children. Aims: The aim of this study was to assess the extent of use of online classroom platforms in early years, both in the private and public sector, and to correlate parents' attitudes towards children’s behavioral changes during the pandemic lockdown in Greece. Methodology: The participants were 216 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Many scholars have studied parents' perceptions of their roles and responsibilities in remote education during the COVID-19 pandemic (e.g., Abuhammad, 2020;Daniela et al, 2021;Karavida & Tympa, 2021). These studies investigated the barriers parents faced in remote education, including a lack of training and support, insufficient technical expertise, a lack of trained personnel (like teachers) to assist them, insufficient communication with teachers and professionals, and a lack of qualifications.…”
Section: Attitudes Toward Remote Education and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars have studied parents' perceptions of their roles and responsibilities in remote education during the COVID-19 pandemic (e.g., Abuhammad, 2020;Daniela et al, 2021;Karavida & Tympa, 2021). These studies investigated the barriers parents faced in remote education, including a lack of training and support, insufficient technical expertise, a lack of trained personnel (like teachers) to assist them, insufficient communication with teachers and professionals, and a lack of qualifications.…”
Section: Attitudes Toward Remote Education and Mental Healthmentioning
confidence: 99%
“…Nevertheless, some parents saw opportunities in remote education, recognizing that digital devices could help children acquire valuable technical skills that will become increasingly important in the future; they were also keen on teaching children how to leverage these resources to improve academic development and future employment prospects (Karavida & Tympa, 2021). While these studies described the varying perceptions of parents regarding remote education, they paid less attention to how parents coped with these changes and its impact on family relationships and their mental health.…”
Section: Attitudes Toward Remote Education and Mental Healthmentioning
confidence: 99%
“…46% of parents of children in the USA were dissatisfied with online learning (Stites et al, 2021). In a quantitative survey of 216 parents of pre-school children, parents were not satisfied with the quality of online teaching (Karavida & Tympa, 2021). A qualitative study involving 50 kindergarten students found that 45 were dissatisfied with online learning and preferred to return to face-to-face learning (Khales, 2022).…”
Section: Introduction Online Teaching and Learning During Covid-19mentioning
confidence: 99%